AdcA and AdcAII employ distinct zinc acquisition mechanisms and contribute additively to zinc homeostasis in Streptococcus pneumoniae. Issue 4 (16th January 2014) - Plumptre, Charles D.; Eijkelkamp, Bart A.; Morey, Jacqueline R.; Behr, Felix; Couñago, Rafael M.; Ogunniyi, Abiodun D.; Kobe, Bostjan; O'Mara, Megan L.; Paton, James C.; McDevitt, Christopher A.
Summary S treptococcus pneumoniae is a globally significant human pathogen responsible for nearly 1 million deaths annually. Central to the ability of S. pneumoniae to colonize and mediate disease in humans is the acquisition of zinc from the host environment. Zinc uptake in S. pneumoniae occurs via the ATP‐binding cassette transporter AdcCB, and, unusually, two zinc‐binding proteins, AdcA and AdcAII. Studies have suggested that these two proteins are functionally redundant, although AdcA has remained uncharacterized by biochemical methods. Here we show that AdcA is a zinc‐specific substrate‐binding protein (SBP). By contrast with other zinc‐binding SBPs, AdcA has two zinc‐binding domains: a canonical amino‐terminal cluster A‐I zinc‐binding domain and a carboxy‐terminal zinc‐binding domain, which has homology to the zinc‐chaperone ZinT from Gram‐negative organisms. Intriguingly, this latter feature is absent from AdcAII and suggests that the two zinc‐binding SBPs of S. pneumoniae employ different modalities in zinc recruitment. We further show that AdcAII is reliant upon the polyhistidine triad proteins for zinc in vitro and in vivo. Collectively, our studies suggest that, despite the overlapping roles of the two SBPs in zinc acquisition, they may have unique mechanisms in zinc homeostasis and act in a complementary manner during host colonization.